Nonlinearity of the Rock Joint Shear Strength - Wei, Y.F.; Fu, W.X.; Nie, D.X. (Проблемы прочности, 2015)
The triaxial testing for irregular or unfilled rock joints was conducted on the rock mechanics test system (MTS). A series of axial failure stresses under different confining pressures applied to the same specimen was continuously acquired on MTS. The corresponding normal and shear stresses acting on the rock joint plane were calculated in terms of LEFM. The Mohr–Coulomb (MC) shear strength parameters of each specimen could be determined by linear regression analysis. Thirteen specimens were taken from the dam site drill rock cores of a hydropower station. The scatter of points plotted for all test results in the normal and shear stress space exhibits obvious nonlinearity. Test results show that it would be more convenient to describe the shear strength of rock joints in the nonlinear form. The comparison and discussion of three function fittings proved that the well-known Barton criterion was more appropriate for describing the shear strength of rock joints.